METODE PENGELOLAAN KONFLIK INTERPROFESIONAL - Mahmasoni Masdar (JURNAL KESEHATAN INDRA HUSADA, 2020)
Introduction: The existence of conflicting goals in patient care cannot be fully agreed upon. Having the ability to manage conflict is good, can help, increase cooperation and increase satisfaction at work. Objective: To identify interprofessional conflict management to increase creativity in carrying out conflict management strategies. Method: The method used in this article is Literature Review. Search based on electronic data, in the selection of articles researchers used themes and analysis in journals. Results: There are several methods that can be done to resolve conflicts, namely: avoidance (collaboration), collaboration, coercion, and negotiation. Conclusion: Conflicts in health workers emphasize the level of stress, satisfaction in work and the effectiveness of teamwork that improve health degradation. Therefore creating creative conflict is a good conflict management strategy.Suggestion: It is hoped that individuals can improve their abilities and knowledge in learning interprofessional conflict management in problem solving. Keywords: Interprofessional Conflict, Conflict Management, Nursing Education